Protecting the rights of women in the ESCWA region through the proper use of UN resolutions and international protocols on war and armed conflict - Mallat, Chibli; United Nations. Economic and Social Commission for Western Asia.; Office of the United Nations High Commissioner for Refugees (New York United Nations, 2009)
"This study examines international human rights instruments and mechanisms related to the protection of the rights of women living in conflict situations and their relevance and applicability in the region of the Economic and Social Commission for Western Asia (ESCWA). It also identifies and examines the physical, economic, social, legal and other challenges facing women living in conflict situations; and makes recommendations to ESCWA member countries and the international community on the development of policies and programmes aimed at protecting the rights of women in conflict situations."-- Executive summary.
International gender law : CEDAW -- The impact of CEDAW : international human rights instruments on the protection of rights of women in conflict situations -- The international criminal and humanitarian law system : from the Geneva Conventions to the ICC -- Case study on displaced Iraqi women -- Conclusions and recommendations.
At head of title: Economic and Social Commission for Western Asia (ESCWA).
E/ESCWA/ECW/2009/1."
"This publication was prepared by Dr. Chibli Mallat. It was coordinated by the Centre for Women in ESCWA, UNHCR, and the Regional Bureau for the Middle East and North Africa."--Acknowledgments
Also available online.
Keywords: Convention on the Elimination of All Forms of Discrimination against Women -- (1980).; Women's rights -- Middle East; Women in war -- Middle East; Women -- Protection -- International cooperation